2013
DOI: 10.1016/j.biotechadv.2013.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the human pluripotent stem cell microenvironment to direct cell fate

Abstract: Human pluripotent stem cells (hPSCs), including both embryonic stem cells and induced pluripotent stem cells, offer a potential cell source for research, drug screening, and regenerative medicine applications due to their unique ability to self-renew or differentiate to any somatic cell type. Before the full potential of hPSCs can be realized, robust protocols must be developed to direct their fate. Cell fate decisions are based on components of the surrounding microenvironment, including soluble factors, subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 177 publications
(241 reference statements)
0
44
0
Order By: Relevance
“…The interactions between hESCs and their surrounding microenvironment are critical for the regulation of inter-and intracellular processes, where subtle changes in this niche can induce dramatic alterations in hESC phenotype [64]. Herein, we have shown that a low (2%)-O 2 atmosphere induced nuclear localization of elevated TERT levels that correlated with hESC proliferation/cell survival in the undifferentiated state, without significantly increasing telomerase activity levels.…”
Section: Discussionmentioning
confidence: 69%
“…The interactions between hESCs and their surrounding microenvironment are critical for the regulation of inter-and intracellular processes, where subtle changes in this niche can induce dramatic alterations in hESC phenotype [64]. Herein, we have shown that a low (2%)-O 2 atmosphere induced nuclear localization of elevated TERT levels that correlated with hESC proliferation/cell survival in the undifferentiated state, without significantly increasing telomerase activity levels.…”
Section: Discussionmentioning
confidence: 69%
“…expressing pancreatic cells. In such a complex step-wise method, efficiency of the target cell production is always a major issue (Hazeltine et al 2013), and pushing the majority of cells into pancreatic differentiation requires every induction step in the process to be highly efficient, including that of definitive endoderm. Many methods to induce definitive endoderm cells from embryonic stem cells (ESCs)/iPSCs have been reported with similar results.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the establishment of human-induced pluripotent stem cells (hiPSCs) (Takahashi and Yamanaka 2006;Takahashi et al 2007) potentially makes it possible to induce appropriate tissues and organs from cells of patients themselves (Drews et al 2012). Pluripotent stem cells (PSCs) have now been made experimentally into almost every cell type by controlling step-wise differentiation with cytokines and by manipulating every microenvironmental condition (Hazeltine et al 2013). However, several obstacles hamper researchers from fully realizing the medical potential of hiPSCs, with the major ones being low induction efficiency and contamination of animal-derived substances.…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 1B present some of such important features, recognised by many authors [18,19], and how they could be reproduced in biomaterials and culturing conditions. The deconstruction of these essential biophysical and structural elements can be reproduced synthetically by the correct design of biomaterialsbased scaffolds that could be then used as frameworks for simplified in vitro niches.…”
Section: Relevant Factors In the Design Of Biomaterialsmentioning
confidence: 98%